2016
DOI: 10.1016/j.molliq.2016.08.097
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structural analysis of hydrated ethylene glycol accounting for the antifreeze effect by using infrared attenuated total reflection spectroscopy

Abstract: To reveal the antifreeze protection mechanism of an aqueous solution of ethylene glycol (EG) at a molecular level, concentration-dependent infrared spectra are analyzed with an aid of chemometrics. The principal component analysis (PCA) of the spectra reveals that the spectral variation is explained by the quantity changes not only of 'bulky water' and the 'bulky EG,' but also of a 'water/EG complex.' After a spectral decomposition using the alternative least squares (ALS) analysis, the spectrum of the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…Despite the reduced contact electrification at the hydrogel–PTFE interface, the two following beneficial effects are obtained using the water–EG mixture in the hydrogel. First, the EG is commercially used as an antifreeze agent, which can reduce the freezing point of the mixture, thereby widening the operation temperature range of the device . Typically, the mixture has the best antifreeze properties with an EG volume percentage around ∼40–60% .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the reduced contact electrification at the hydrogel–PTFE interface, the two following beneficial effects are obtained using the water–EG mixture in the hydrogel. First, the EG is commercially used as an antifreeze agent, which can reduce the freezing point of the mixture, thereby widening the operation temperature range of the device . Typically, the mixture has the best antifreeze properties with an EG volume percentage around ∼40–60% .…”
Section: Resultsmentioning
confidence: 99%
“…First, the EG is commercially used as an antifreeze agent, which can reduce the freezing point of the mixture, thereby widening the operation temperature range of the device. 42 Typically, the mixture has the best antifreeze properties with an EG volume percentage around ∼40−60%. Therefore, the water-to-EG ratio was selected as 3:2 for the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…Where, the adding of suitable antifreeze additives into aqueous solutions can reduce the freezing point and other parameters such as the low viscosity and wide liquid range, which impact on the improvement of the low-temperature performance of aqueous battery systems. Furthermore, it can be suggested that adding EtG into aqueous electrolyte solutions on the surface of the LiFePO 4 materials can form a complex of aqueous electrolyte solution and EtG . In the case of using the EtG as an antifreeze agent that is an organic additive, the low-temperature performance of the LiFePO 4 materials is superior to those without the EtG.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our previous study found that the types of the excipients used in candesartan cilexetil tablets differ depending on the manufacturer, and Raman spectra of the tablets showed the different pattern reflecting the chemical nature of the excipients. 34 Here, we focused on the methodology for detecting substandard and falsified medicines by principal component analysis (PCA) 12,22,[35][36][37][38][39][40][41][42][43] of raw data obtained by handheld Raman spectroscopy. We aimed to clarify the chemical features of substandard medicines by comparing them with authentic medicines, and by extracting the principal components of the Raman spectrum to visualize the relationships among the tablets.…”
Section: Introductionmentioning
confidence: 99%